Thymic mucoepidermoid carcinoma: a clinicopathologic and molecular study - Murase, Takayuki; Nakano, Satsuki; Sakane, Tadashi; Domen, Hiromitsu; Chiyo, Masako; Nagasaka, Satoshi; Tanaka, Michio; Kawahara, Yutaka; Toishi, Masayuki; Tanaka, Takuji; Nakamura, Shota; Sawabata, Noriyoshi; et al. (The American journal of surgical pathology, 2022)
Thymic mucoepidermoid carcinoma (MEC) is a rare tumor, and its characteristics remain to be clarified. Here we investigated 20 cases of thymic MEC to systematically characterize its clinical, histopathologic, and molecular features. The median age of the patients was 56 years (range, 19 to 80 y), there was a slight male predilection (3:2), and 44% of the patients were asymptomatic at diagnosis. The median tumor size was 6.8 cm in diameter, 55% were pT1 tumors, and 50% were TNM stage I tumors. When 4 tumor grading systems for salivary MEC (Armed Forces Institutes of Pathology, Brandwein, modified Healey, and the Memorial Sloan-Kettering) were employed, low-grade, intermediate-grade, and high-grade tumors accounted for 35% to 70%, 5% to 25%, and 25% to 50%, respectively. Many histologic variants were noted, and 70% of the cases were classified as nonclassic variants. MAML2 rearrangement was detected in 56% of cases, and the fusion partner was CRTC1 in all cases. CRTC1-MAML2 fusion was associated with lower pT classification and lower TNM stage. The overall survival rate of all patients was 69% and 43% at 5 and 10 years, respectively. Worse overall survival was associated with higher pT stage, higher TNM stage, residual tumors, greater tumor size, high-grade tumor histology (Armed Forces Institutes of Pathology and Memorial Sloan-Kettering, but not the other 2), and with the absence of CRTC1-MAML2 fusion. Of note, none of the patients with CRTC1-MAML2 fusion-positive tumors died during the follow-up. In conclusion, the clinicopathologic and molecular findings of thymic MEC presented here are expected to contribute to the management of this rare tumor.
Gesehen am 30.10.2023